Modeling training loads and injuries: The dangers of discretization - Carey, D. L.; Crossley, K. M.; Whiteley, R.; Mosler, A.; Ong, K. L.; Crow, J.; Morris, M. E. (Medicine & Science in Sports & Exercise, 2018)
Purpose To evaluate common modeling strategies in training load and injury risk research when modeling continuous variables and interpreting continuous risk estimates; and present improved modeling strategies.